1992
DOI: 10.1113/jphysiol.1992.sp019439
|View full text |Cite
|
Sign up to set email alerts
|

Role of M1 muscarinic receptors in the parasympathetic control of colonic motility in cats and rabbits.

Abstract: SUMMARY1. The effects of pirenzepine (a selective blocking agent of M1 muscarinic receptors) were studied on excitatory junction potentials (EJPs) and inhibitory junction potentials (IJPs) elicited on colonic smooth muscle by stimulation of efferent parasympathetic nerve fibres in anaesthetized cats and rabbits.2. Pirenzepine (25,tg kg-' to 0-2 mg kg-', i.v.) decreased the amplitude of EJPs or abolished them. In pirenzepine, parasympathetic stimulation elicited IJPs in most cases.3. In both species, pirenzepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Three subtypes of muscarinic receptors (M1, M2 and M3) have been identified by using selective receptor antagonists. The dosage of M1 muscarinic receptors antagonist-pirenzepine used in this study was 10 mg/kg, a dose much higher than that used in other studies (Barocelli et al, 1995;Blanquet and Gonella, 1992;Dal Monte et al, 1985). The major difference between other studies and ours is the route of administration of pirenzepine, which was given by intravascular injection in the former studies whereas by oral route in the latter one.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Three subtypes of muscarinic receptors (M1, M2 and M3) have been identified by using selective receptor antagonists. The dosage of M1 muscarinic receptors antagonist-pirenzepine used in this study was 10 mg/kg, a dose much higher than that used in other studies (Barocelli et al, 1995;Blanquet and Gonella, 1992;Dal Monte et al, 1985). The major difference between other studies and ours is the route of administration of pirenzepine, which was given by intravascular injection in the former studies whereas by oral route in the latter one.…”
Section: Discussionmentioning
confidence: 92%
“…Whereas the significant effect of atropine was on the modification of the frequency of the phasic contractions, but only for a short period of time (Garrigues et al, 1986). In addition, M1 muscarinic receptors are involved in synaptic transmission within intramural plexuses, at synapses in the parasympathetic excitatory pathway to colonic smooth muscle, but are not involved in the pathway to the NANC inhibitory neurons (Blanquet and Gonella, 1992). Under normal physiological conditions, NANC neurones are tonically inhibited by an intramural nervous circuit involving M1 muscarinic receptors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of these, at least three subtypes of muscarinic receptor have been implicated in smooth muscle cholinergic regulation in different animal species. Ml receptors, probably located on the intramural nervous inhibitory circuit present on neuron -smooth muscle fibre junctions in rabbits, cats, dogs, and other species, play a role in the vagal regulation (Cosentino et al 1992;Killingsworth and Robinson 1992;Blanquet and Gonella 1992;De Ponti et aH. 1993).…”
Section: Drugsmentioning
confidence: 98%
“…Electrical stimulation of the vagal nerves or pelvic efferents innervating the stomach and intestine caused muscle contractions which were inhibited by muscarinic receptor antagonists and blockers of neuronal depolarization [100, 101]. Studies with selective muscarinic antagonists and muscarinic receptor knockout mice concluded M 3 muscarinic receptors are the dominant subtype mediating intestinal motility [102, 103].…”
Section: Parasympathetic Control Of the Intestinementioning
confidence: 99%